2017
DOI: 10.3390/ijerph14121572
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Factors for Sustaining Open Defecation-Free Communities in Rural Indonesia: A Cross-Sectional Study

Abstract: Community Approaches to Total Sanitation (CATS) programmes, like the Sanitasi Total Berbasis Masyarakat (STBM) programme of the Government of Indonesia, have played a significant role in reducing open defecation though still little is known about the sustainability of the outcomes. We assessed the sustainability of verified Open Defecation Free (ODF) villages and explored the association between slippage occurrence and the strength of social norms through a government conducted cross-sectional data collection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 32 publications
8
55
3
2
Order By: Relevance
“…The analysis revealed that the open defecation-free slippage rate in Ethiopia was 15.9% (95% CI 12.9–19.4%). This slippage rate was higher than a study conducted in Nepal 3.5% [ 40 ], in Ghana 8.8% [ 41 ], and in Indonesia 14.5% [ 42 ], consecutively. Similarly, the slippage rate was higher than the average slippage rate of some African countries, which was 10–13% [ 2 , 43 ], in contrast, lower than East Timor 16.4% [ 44 ], Benin 17.5%, Mali and Mauritania 24% [ 41 ], Kenya 22% [ 2 ], Eritrea 27% [ 45 ], and Mozambique 31% [ 46 ] (Fig.…”
Section: Discussioncontrasting
confidence: 61%
“…The analysis revealed that the open defecation-free slippage rate in Ethiopia was 15.9% (95% CI 12.9–19.4%). This slippage rate was higher than a study conducted in Nepal 3.5% [ 40 ], in Ghana 8.8% [ 41 ], and in Indonesia 14.5% [ 42 ], consecutively. Similarly, the slippage rate was higher than the average slippage rate of some African countries, which was 10–13% [ 2 , 43 ], in contrast, lower than East Timor 16.4% [ 44 ], Benin 17.5%, Mali and Mauritania 24% [ 41 ], Kenya 22% [ 2 ], Eritrea 27% [ 45 ], and Mozambique 31% [ 46 ] (Fig.…”
Section: Discussioncontrasting
confidence: 61%
“…Programs like CLTS may have improved coverage, but improved coverage may not equate to improved levels of usage in the context of large-scale programs (48). The poorest commonly revert back to open defecation due to low-quality sanitation structures that are prone to collapse, or ll with no provision for emptying (52)(53)(54). Many latrines built as part of CLTS are unimproved and shared; they do not effectively remove waste from the environment and are not sustainable (55).…”
Section: Discussionmentioning
confidence: 99%
“…A correlation in lack of handwashing with soap and ODF slippage was established at 8% (Shivanarain & Nancy, 2015). A cross sectional study to ascertain the association of ODF slippage and the strength of social norms in Indonesia for 587 households after a two-year ODF period estimated the slippage rate at 14.5% (Odagiri, et al, 2017).…”
Section: Example 2: Village Populationmentioning
confidence: 99%
“…ODF slippage occurs when one or more toilet adequacy parameters are no longer present for one or more toilets in a community (Galan, et al, 2013;Njuguna & Muruka, 2017). It is increasingly recognised that maintaining ODF status is challenging due to uncertainties in social cohesion, implementing agencies and government priorities, sustainability of toilet and handwashing technologies, sanitation financing, governance, monitoring and sanitation markets (Bongartz, 2016;Odagiri, et al, 2017). Faced with the challenge of ODF slippage, there is limited scientific evidence to guide a systematic approach on mitigating ODF slippage risk factors and covariates.…”
Section: Introductionmentioning
confidence: 99%